Dynamic Responses of Phosphorus Metabolism to Acute and Chronic Dietary Phosphorus-Limitation in Daphnia - Wagner, Nicole D.; Prater, Clay; Frost, Paul C. (Frontiers in Environmental Science, 2017)
Food quality is highly dynamic within lake ecosystems and varies spatially and temporally over the growing season. Consumers may need to continuously adjust their metabolism in response to this variation in dietary nutrient content. However, the rate of metabolic responses to changes in food nutrient content has received little direct study. Here, we examine responses in two metabolic phosphorus (P) pools, ribonucleic acids (RNA), and adenosine triphosphate (ATP) along with body mass and body P content in Daphnia magna exposed to chronic and acute dietary P-limitation. First, we examined food quality effects on animals consuming different food carbon (C):P quality over a 14 day period. Then, we raised daphnids on one food quality for 4 days, switched them to contrasting dietary treatments, and measured changes in their metabolic responses at shorter time-scales (over 48 h). Animal P, RNA, and ATP content all changed through ontogeny with adults containing relatively less of these pools with increasing body mass. Irrespective of age, Daphnia consuming high C:P diets had lower body %P, %RNA, %ATP, and mass compared to animals eating low C:P diets. Diet switching experiments revealed diet dependent changes in body %P, %RNA, %ATP, and animal mass within 48 hours. We found that Daphnia switched from low to high C:P diets had some metabolic buffering capacity with decreases in body %P occurring after 24 h but mass remaining similar to initial diet conditions for 36 h after the diet switch. Switching Daphnia from low to high C:P diets caused a decrease in the RNA:P ratio after 48 h. Daphnia switched from high to low C:P diets increased their body P, RNA, and ATP content within 8-24 h. This switch from high to low C:P diets also led to increased RNA:P ratios in animal bodies. Overall, our study revealed that consumer P metabolism reflects both current and past diet due to more dynamic and rapid changes in P biochemistry than total body mass. This metabolic flexibility is likely linked to resource integration in D. magna, which reduces the negative effects of short-term or variable exposure to nutrient-deficient foods.